Effects of light variation on Schwalbe's line‐based anterior chamber angle metrics measured with cirrus spectral domain optical coherence tomography. (14th March 2016) - Marion, Kenneth M; Niemeyer, Moritz; Francis, Brian; Sadda, Srinivas R; Chopra, Vikas
Abstract: Background: Evaluate the impact of variations in ambient lighting conditions on the reproducibility/reliability of Schwalbe's Line (SL)‐based anterior chamber angle (ACA) metrics using spectral domain optical coherence tomography (SD‐OCT). Design: Images were taken at Doheny Eye Centers‐UCLA clinic, which were randomized, masked and graded twice by dual reading centre graders. Participants: Twenty‐five normal/healthy participants with open angles Methods: Inferior angles were imaged using Cirrus SD‐OCT under five light levels (foot‐candles (fc) measured at camera‐eye interface with Sper light‐meter) with the instrument's corneal illumination function set to default level of 50 (CIdef) and low 5 (CIlow). Each eye was imaged 20 times, totaling 500 assessments. Main Outcome Measures: SL‐angle‐opening‐distance (SL‐AOD) and SL‐trabecular‐iris‐space‐area (SL‐TISA) measured using custom ImageJ software. Intra‐/inter‐grader variability analyses were completed using Statistical‐Package‐for‐Social‐Science and Bland–Altman plots demonstrated limits of agreement for comparisons. Results: Light level demonstrated a linear relationship with angle size, thus differences from highest to lowest light levels were compared. Decreasing light from 1.0 → 0.0fc at CIdef decreased SL‐AOD from 394 µm +/− 137 µm → 356 µm +/− 137 µm (mean percent difference (MPD) = 10.71%, P  < 0.001) and SL‐TISA from 297 µm 2  +/− 114 µm 2  → 261 µm 2  +/− 109 µm 2 (MPD = 13.7%, P  < 0.001). Decreasing from 1.0 → 0.0fc at CIlow decreased SL‐AOD from 366 µm +/− 136 µm → 329 µm +/− 122 µm (MPD = 10.9%, P  < 0.001) and SL‐TISA from 271 µm 2  +/− 113 µm 2  → 234 µm 2  +/− 98 µm 2 (MPD = 15.8%, P  < 0.001). There was 7.9/11.4% (both P  < 0.001) difference for SL‐AOD/SL‐TISA between CIdef → CIlow at 1.0fc, and 7.7/9.4% (both P  < 0.001) difference at 0.0fc. Intra‐/inter‐grader results showed high reproducibility for all metrics (MPD = 0.33–4.4%; CV = 0.96–1.36; PCC = 0.93–0.95( P  < 0.001); R2 = 0.94–0.98). Bland–Altman plots did not demonstrate bias, with repeat‐ability and agreement among measurements. Conclusions: Using Cirrus SD‐OCT, we found that SL‐based ACA morphometrics are exquisitely sensitive to changes in ambient illumination and also corneal illumination by the OCT instrument. Consistently imaging in the darkest room possible is recommended (≤0.2 fce).